Scientific approaches to the development of the industry standard of the land management projects for the organization of the territory of the scientific institutions, the lands of which have been allocated for agricultural research and educational activities - Dorosh, Y.; Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2020)
Legislation that regulated land ten years ago requires a comprehensive update and systematic approach to the development of standards, rules and restrictions. The article substantiates the need to improve the legislative support of land management. The conceptual approach to the formation of normative legal support in the field of land management is proposed, which is based on the principles of systematicity, planning and optimality. This approach is based on the standardization and unification of types of land management documentation, taking into account the particularities of land use according to their main purpose. The distribution of land categories by main purpose in accordance with the Land Cadastre of Ukraine is shown, which should be the basis for the creation and improvement of standards and rules in land use. Scientific approaches are grounded, in accordance with the improved system of legislative support of land management, to the development, composition and content of the industry standard of the project of land management regarding the organization of the territory of scientific institutions, the lands of which are allocated for agricultural research and educational activities. Such standards must establish rules and regulations for the use of land for the intended purpose and uses, and must be taken into account when developing land use documentation standards. Key words: land management, lands for agricultural research and educational activities, land category, type of use, land management project, organization of the territory, land use, main purpose.